Sustaining and Impeding Factors of Microfinance Services for Micro-enterprises Development - Ph. Romen Sharma , Rashmi Singh , Shantanu Kumar Dubey; Shridhar Patil (Indian Journal of Extension Education, 2013)
The present study examines the sustaining and impeding factors of the microfinance services as perceived by the beneficiaries and dropout clients, and it also investigates the reason for not availing the microfinance services by the nonbeneficiaries. Study included 40 microfinance beneficiaries, 30 microfinance drop-outs and 30 non-beneficiaries constituting the total sample of 100 respondents. Responses of the subjects were collected through an open ended questionnaire. Garrett’s ranking was used to rank order the factors. The study revealed that ease of access and related services of micro-credit at village level and lower capital interest rate were the sustaining factors whereas insensitivity of microfinance institution (MFI) to type of enterprises, business cycle, clients’ socio-economic and -personal circumstances; the norm of weekly repayments and savings pressure were the impeding factors. Fear of losing their property at default repayment and perceived weekly repayments pressure were the reasons for not availing the microfinance services.